PD-1 and TIGIT Are Highly Co-Expressed on CD8+ T Cells in AML Patient Bone Marrow - Xu, Ling; Liu, Lian; Yao, Danlin; Zeng, Xiangbo; Zhang, Yikai; Lai, Jing; Zhong, Jun; Zha, Xianfeng; Zheng, Runhui; Lu, Yuhong; Li, Minming; Jin, Zhenyi; et al. (Frontiers in Oncology, 2021)
Despite the great success of immune-checkpoint inhibitor (ICI) treatment for multiple cancers, evidence for the clinical use of ICIs in acute myeloid leukemia (AML) remains inadequate. Further exploration of the causes of immune evasion in the bone marrow (BM) environment and peripheral blood (PB), understanding how T cells are affected by AML induction chemotherapy or the influence of age may help to select patients who may benefit from ICI treatment. In this study, we comprehensively compared the distribution of PD-1 and TIGIT, two of the most well-studied IC proteins, in PB and BM T cells from AML patients at the stages of initial diagnosis, complete remission (CR), and relapse-refractory (R/R) disease after chemotherapy. Our results show that PD-1 was generally expressed higher in PB and BM T cells from de novo (DN) and R/R patients, while it is partially recovering in CR patients. The expression of TIGIT increased in the BM of CD8+ T cells from DN and R/R patients, but it did not recover with CR. In addition, according to age correlation analysis, we found that elderly AML patients possess an even higher percentage of PD-1 and TIGIT single-positive CD8+ T cells in PB and BM, which indicate more significant impairment of T cell function in elderly patients. In addition, we found that both DN and R/R patients accumulate a higher frequency of PD-1+ and TIGIT+ CD8+ T cells in BM than in corresponding PB, indicating that a more suppressive microenvironment in leukemia BM may promote disease progression. Collectively, our study may help guide the combined use of anti-PD-1 and anti-TIGIT antibodies for treating elderly AML patients and pave the way for the exploration of strategies for reviving the BM microenvironment to improve the survival of AML patients.